Visuality and Its Discontents: Novels on Screen and the Case of "The French Lieutenant's Woman" - Jukić, Tatjana (Array, 2003)
Uneasy meeting points of literature and visuality dominate most discussions of novels on film. The case of The French Lieutenant’ s Woman (Fowles/ Reisz) has the value of their synecdoche, since its very story manages various joint histories and economies of literature and the visual. My presentation focuses on the historicity of these joint practices, and the ways in which they accumulate and affect the rhetoric of film.